2003
DOI: 10.1034/j.1399-0004.2003.00077.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of splice‐site mutations of the α‐galactosidase A gene in Fabry disease

Abstract: Fabry disease is an X-linked disease caused by a defective lysosomal enzyme, alpha-galactosidase A, and characterized by skin lesions and multiorgan involvement, including kidney, heart, and the central nervous system. Currently more than 200 genotypes have been identified, including several aberrant splicing. However, most of the mutation analyses were performed using genomic sequencing only, and therefore some of the splicing mutations were misclassified as missense mutations. In order to predict the splicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…17,19 Perhaps gene mutational analysis could be helpful in this regard, as over 200 mutations have been described in Fabry disease alone. 27 Alternatively, our patient's lipid droplets may represent a very early manifestation of a glomerular disorder, such as minimal change disease. 28 Regardless, his renal function will need to be monitored.…”
Section: Electron Microscopymentioning
confidence: 96%
“…17,19 Perhaps gene mutational analysis could be helpful in this regard, as over 200 mutations have been described in Fabry disease alone. 27 Alternatively, our patient's lipid droplets may represent a very early manifestation of a glomerular disorder, such as minimal change disease. 28 Regardless, his renal function will need to be monitored.…”
Section: Electron Microscopymentioning
confidence: 96%
“…The overexpression of a cryptic exon in intron 4, leading to extremely unbalanced ratios of the c.639ins + 57 over the wildtype GLA transcript, has already been identified as the underlying cause of deficient αGal activity in ( The hypothesis that the non-canonical c.639ins + 57 GLA transcript is overexpressed in patients carrying the g.9331G > A SNP due to increased recognition of the alternative splicing by an A/C-rich enhancer-type ESE (4), generated by the G > A transition, has been disputed (22) since that SNP occurs at a non-consensus site of the cryptic donor splice site and there are no functional ESE motifs (23) within the surrounding intronic region. Bioinformatic analyses of the g.9273C > T variant indicated that this transition does not significantly change the predicted acceptor site score, in comparison to the wildtype sequence, and that the highly predominant expression of the c.639ins + 57 transcript might be explained by the creation of a novel ESE (8).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed analysis of cDNA by reverse transcriptase PCR (RT-PCR) represents a powerful tool for searching causative splicing mutations or gene rearrangements. This strategy is applied with disease-related genes in patients who do not show mutations in the coding regions at the DNA level [9,10]. The same strategy was previously applied as the first-line mutation screening method for the F8 and F9 genes [11][12][13].…”
Section: Detailed Mrna Studymentioning
confidence: 99%